Prevalence of primary drug resistant tuberculosis in a tertiary care hospital, Nepal - Khunjeli, R; Mohsin, U R; Shrestha, S K; Adhikari, S; Srivastava, B; Shrestha, B (Journal of Chitwan Medical College, 2015)
Background & objectives: Tuberculosis is a transmissible disease mainly due to inhalation of infected droplet nuclei. The burden of drug resistant tuberculosis is very high in our neighboring countries India and China. Prevalence of primary drug resistant disease is difficult to estimate in our country because culture and sensitivity is not done routinely. This study was an attempt to find out the prevalence of drug resistant in newly diagnosed tuberculosis patients serving in the Nepalese Armed Forces. Methodology: Medical records of patients serving in the Nepalese Armed Forces who had the provisional diagnosis of pulmonary tuberculosis for the first time from July 2012 to June 2014 were analyzed. They had their sputum subjected for both smear and culture with sensitivity testing. Out of 134 patients, 62 had culture positive for Mycobacterium tuberculosis and drug sensitivity was done for the first line 4 antitubercular drugs. Results: Drug resistant strains were found in 5 cases (8.1%) of which 2 (3.2%) were resistant to 4 first line drugs - rifampicin, isoniazid, ethambutol and streptomycin. Prevalence of isoniazid resistance was the highest, found in 3 cases (4.8%). Conclusion: Primary drug resistant tuberculosis in newly diagnosed cases was high even in young healthy adults, and isoniazid resistant strains were the commonest. DOI: http://dx.doi.org/10.3126/jcmc.v4i4.11970